Faba bean as a novel brewing adjunct: Consumer evaluation. Issue 3 (10th May 2019) - Black, Kirsty; Barnett, Andrew; Tziboula‐Clarke, Athina; White, Philip J.; Iannetta, Pietro P.M.; Walker, Graeme
Abstract : The starch in the grains of legumes, such as faba bean ( Vicia faba L.), offers an environmentally sustainable raw material for the brewing industry as their entire nitrogen fertiliser requirement can be provided by the natural process of biological nitrogen fixation. Faba bean is, therefore, distinguished from species such as spring barley ( Hordeum vulgare L.), which require large amounts of synthetic nitrogen fertiliser. Consumer analysis of beer produced with faba bean as an adjunct compared with barley malt beers has not previously been assessed. This study evaluated the potential of beers brewed using 30% (w/w) dehulled bean (kernel) flour as an adjunct to malted barley, using a series of quantitative sensory tests. The first, a blind acceptance test with inferred preference, found no statistically significant difference in the taste score of the bean kernel flour adjunct beer when compared with conventional beer. In the second acceptance test, the knowledge that the beer was produced using beans did not affect the overall consumer impression of the beer, regardless of how this information was presented. These results suggest that the use of faba beans in brewing does not impact negatively on the taste or acceptability of the resultant beer. © 2019 The Institute of Brewing & Distilling